Stress models of depression: forming genetically vulnerable strains - Henn, Fritz A.; Vollmayr, Barbara (Neuroscience & biobehavioral reviews, 2005)
Among the most useful models for depressive disorders are those, which involve a stress induced change in behaviour. Learned helplessness is one such model and is induced through exposure to uncontrollable and unpredictable aversive events. Learned helplessness as induced in rats using foot shock is well characterized and has good face validity and predictive validity as a model of depression, including alterations in HPA axis activity and REM sleep characteristic of depression. The data concerning the validity will be briefly reviewed. The model can also be used to look at the role of genetics through selective breeding. These studies will be reviewed and the utility of the genetic strains for understanding the interaction of stress and affect will be examined. A second model of depression using exposure to chronic stress also has high face and predictive validity. A new form of this approach, recently described, also is suitable for the examination of genetic factors leading to depressive like behaviour and this will be presented.
Gesehen am 21.10.2020